F9 mRNA splicing aberration due to a deep Intronic structural variation in a patient with moderate hemophilia B. Issue 213 (May 2022) - Odaira, Koya; Kawashima, Fumika; Tamura, Shogo; Suzuki, Nobuaki; Tokoro, Mahiru; Hayakawa, Yuri; Suzuki, Atsuo; Kanematsu, Takeshi; Okamoto, Shuichi; Takagi, Akira; Katsumi, Akira; Matsushita, Tadashi; et al.
Abstract: Introduction: Hemophilia B (HB) is a hereditary bleeding disorder caused by the genetic variation of the coagulation factor IX (FIX) gene ( F9 ). Several F9 structural abnormalities, including large deletion and/or insertion, have been observed to cause HB development. However, there is limited information available on F9 deep intronic variations. In this study, we report about a novel large deletion/insertion observed in a deep region of F9 intron 1 that causes mRNA splicing abnormalities. Patient and methods: The patient was a Japanese male diagnosed with moderate HB (FIX:C = 3.0 IU/dL). The genomic DNA of the patient was isolated from peripheral blood leukocytes. DNA sequences of F9 exons and splice donor/acceptor sites were analyzed via polymerase chain reaction and Sanger sequencing. Variant-affected F9 mRNA aberration and FIX protein production, secretion, and coagulant activity were analyzed by cell-based exon trap and splicing-competent FIX expression vector systems. Results: A 28-bp deletion/476-bp insertion was identified in the F9 intron 1 of a patient with moderate HB. A DNA sequence identical to a part of the inverted HNRNPA1 exon 12 was inserted . Cell-based transcript analysis revealed that this large intronic deletion/insertion disrupted F9 mRNA splicing pattern, resulting in reduction of protein-coding F9 mRNA. Conclusion: A novel deep intronic F9 rearrangement was identified in a Japanese patient with moderate HB. Abnormal F9 mRNA splicing pattern due to this deep intronic structural variation resulted in a reduction of protein-coding F9 mRNA, which probably caused the moderate HB phenotype. Highlights: An F9 intronic structural variation was found in a moderate hemophilia B patient. A part of inverted HNRNPA1 exon 12 was inserted into the F9 deep intron 1. This F9 deep intronic variation caused aberrant F9 mRNA splicing. The splicing aberration caused a reduction in the protein-coding F9 mRNA. The F9 deep intron 1 structural variation resulted in a reduction of FIX production.